2008
DOI: 10.1152/japplphysiol.00819.2007
|View full text |Cite
|
Sign up to set email alerts
|

Muscle phosphocreatine kinetics in children and adults at the onset and offset of moderate-intensity exercise

Abstract: The splitting of muscle phosphocreatine (PCr) plays an integral role in the regulation of muscle O2 utilization during a "step" change in metabolic rate. This study tested the hypothesis that the kinetics of muscle PCr would be faster in children compared with adults both at the onset and offset of moderate-intensity exercise, in concert with the previous demonstration of faster phase II pulmonary O2 uptake kinetics in children. Eighteen peri-pubertal children (8 boys, 10 girls) and 16 adults (8 men, 8 women) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
38
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 64 publications
4
38
0
Order By: Relevance
“…A PCr slow component was identified in children for the first time, and found to be similar in amplitude to the slow component in adults. Consistent with the findings of Barker et al (12) for moderate-intensity exercise, metabolic control appears to be adult-like in 13 yr old children during high intensity exercise. The kinetics of muscle HHb, measured using NIRS, were significantly faster in children than adults, implying that oxygen delivery is less closely matched to oxygen extraction in children at the onset of exercise.…”
Section: Considerationssupporting
confidence: 90%
See 1 more Smart Citation
“…A PCr slow component was identified in children for the first time, and found to be similar in amplitude to the slow component in adults. Consistent with the findings of Barker et al (12) for moderate-intensity exercise, metabolic control appears to be adult-like in 13 yr old children during high intensity exercise. The kinetics of muscle HHb, measured using NIRS, were significantly faster in children than adults, implying that oxygen delivery is less closely matched to oxygen extraction in children at the onset of exercise.…”
Section: Considerationssupporting
confidence: 90%
“…A recent 31 P-MRS study by Barker and colleagues (12) has shown that the kinetics of muscle PCr during moderate intensity exercise, i.e. below the inorganic phosphate(P i )/PCr intracellular threshold (IT), are similar between children and adults, implying that the phosphate-linked control of cellular respiration is adult-like in children during moderate intensity exercise.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have recently reported 31 P MRS results recorded during repeated square-wave exercises (9,26,27). This procedure was used in order to improve the reliability of metabolic measurements and is actually similar to what is commonly performed for the V O 2p kinetics response (28), which exhibits inherent irregularities in gas exchange due to breath by breath fluctuations.…”
mentioning
confidence: 99%
“…On that basis, the initial rate of PCr recovery and the maximum aerobic capacity should be considered as additional indexes to compare the post-exercise PCr recovery rate and mitochondrial oxidative capacity across different populations when end-of-exercise pH and PCr concentration values are different or not taken into account. This was the case in some previously published studies that investigated in vivo mitochondrial function from childhood to young and/or late adulthood (5,6). In contrast, this was not the case in other studies that investigated age-related changes in mitochondrial oxidative capacity from childhood to adulthood (7) and examined the association between mitochondrial alterations and insulin sensitivity in overweight and normal-weight children (8).…”
mentioning
confidence: 91%